PROCESSING ZIRCONIA THROUGH ZIRCON SAND SMELTING WITH NaOH AS A FLUX - Yuhelda Yuhelda; Dessy Amalia; Enggan P. Nugraha (Indonesian Mining Journal, 2016)
Zirconia had been made through smelting the zircon sand along with NaOH as a flux. The zircon sand as the smelter feed was taken from CV. Kurnia Alam Sejati mine at Palangkaraya, Middle Kalimantan. Major content of the zircon sand was 28.04% ZrO2 and SiO2 51.22% with several minor oxides such as 0.54% HfO2, 2.53% Fe2O3, 10.53% TiO2, 3.27% Al2O3 and less than 1% of alkali, alkaline earth and rare earth elements. In order to economizing the process, zircon sand upgrading was conducted prior to zirconia production. The upgrading process was conducted using several comprehensive equipments, consist of shaking table, magnetic separator and high tension separator (HTS).The upgraded sand contained 65.35% of ZrO2+HfO2 with 73.25% recovery, which was then used for smelting process at 650C for 2 hours using NaOH as a flux. The product was then leached with water and sulphuric acid then crystallized to get precipitated zirconium hydroxide. The precipitated product was calcined at 900C for 1 hour to get the zirconia and analyzed for its content. The zirconia content was 97.27% of ZrO2+HfO2 with 65.13% recovery.